The Abdominal Aortic Intima-Media Thickness Increases in Patients with Primary Hyperparathyroidism - Sumbul, Hilmi Erdem; Koc, Ayse Selcan (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background We aimed to determine whether there is an increase in aortic intima-media thickness values measured from the abdominal aorta in addition to the traditional carotid intima-media thickness in patients with primary hyperparathyroidism and to determine the parameters closely related to aortic intima-media thickness.Methods This perspective study included 65 primary hyperparathyroidism patients and 30 healthy-controls. Routine laboratory tests for the diagnosis of hyperparathyroidism and vascular ultrasound examinations were performed. Common carotid, internal carotid, and abdominal aortic intima media thickness were measured. The participants of the study was divided into 3 groups as the control (Group–I), the medical treatment (Group–II) due to primary hyperparathyroidism, and the planned surgery (group–III).Results Aortic intima-media thickness, serum urea, creatinine, glucose, uric acid, hs-CRP, parathyroid hormone, calcium and urine calcium levels increased significantly from Group–I to Group–III and T–scores and serum phosphorus in levels decreased significantly. Carotid intima-media thicknesses were not significantly different between the groups. Serum and urinary calcium levels were independently associated with aortic intima-media thickness. Aortic intima-media thickness, serum phosphorus, parathyroid hormone, T-scores, serum and urinary calcium levels are independent indicators for Group–III. When the cut-off value of aortic intima-media thickness was taken as 1.5 mm, 80.6% sensitivity and 89.1% specificity were determined for patients who would go to surgery.Conclusion Serum and urine calcium levels were independently associated with aortic intima-media thickness. Aortic intima-media thickness is more useful than carotid intima-media thickness in showing vascular organ involvement in patients with primary hyperparathyroidism.
Keywords: primary hyperparathyroidism; aortic intima-media thickness; parathyroid hormone